Strategi Pengembangan Kapabilitas Organisasional Dalam Era Digital Fokus Pada Adaptasi Dan Inovasi - Rilly Lesnussa; Vip Pramarta; Carlof Carlof; Rabiah Demlinur Putri; Muh. Muchni Desara (Journal of Management and Creative Business, 2023)
Discusses the strategy of developing organizational capabilities in the digital era, with a focus on organizational adaptation and innovation in the face of rapid digital changes. In this era, organizations must be capable of anticipating and adjusting to technological advancements, changes in consumer behavior, and increasingly complex market demands. The development of adaptive and innovative organizational capabilities is key to achieving competitive advantage. explains the concept of organizational capabilities in the digital era and identifies the challenges faced by organizations in developing their capabilities. These challenges include digital transformation, organizational cultural changes, change management, cybersecurity, and the integration of new technologies into organizational operations. Furthermore, the benefits of using digital technology in developing organizational capabilities. The benefits derived from this include improved operational efficiency, product and service innovation, enhanced customer relationships, and better access to information for decision-making. Additionally, presents a case study on the implementation of a strategy for developing organizational capabilities in the digital era by Organization X. The study analyzes how Organization X overcame challenges, implemented appropriate strategies, and reaped the benefits of digital technology utilization. In conclusion, emphasizes the importance of developing organizational capabilities in the digital era and identifies strategies that organizations can employ to achieve competitive advantage. In this ever-evolving era, organizations must adopt adaptive and innovative strategies to remain relevant and successful amidst digital changes.